2019
DOI: 10.1590/1980-5373-mr-2019-0389
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Recycling Process to Recover Fiber from Fiberglass Polyester Composites

Abstract: Fiberglass/thermoset matrix composite present important properties, such as specific mass and mechanical strength, aiming to replace some engineering materials. However, its mixture of different materials transforms them into an environmental problem, due to the complex recycling process. The highlight is meeting the demands of environmental pressures and for establishing recycling mechanisms, the proposal is to study physical recycling processes, focusing on the microwave-assisted pyrolysis process and also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The fibers are then contained in the air flow, and can be separated. The pyrolysis processes can involve microwave heating for polymer degradation [ 94 , 95 ]. Åkesson et al [ 94 ] studied microwave pyrolysis of wind turbine blades, and observed that glass fibers lost about 25% of their strength.…”
Section: Recycling Of Wind Turbine Bladementioning
confidence: 99%
“…The fibers are then contained in the air flow, and can be separated. The pyrolysis processes can involve microwave heating for polymer degradation [ 94 , 95 ]. Åkesson et al [ 94 ] studied microwave pyrolysis of wind turbine blades, and observed that glass fibers lost about 25% of their strength.…”
Section: Recycling Of Wind Turbine Bladementioning
confidence: 99%
“…Several studies [46][47][48] report the application of the microwaves for heating the waste in order to decompose the matrix into gasses and oil. The results showed higher calorific values than the amount of energy used for the recycling process.…”
Section: Pyrolysismentioning
confidence: 99%
“…Compared with other heat treatment methods, microwave offers the benefits of using less energy to achieve fast heat transfer, contactless and selective heating for complex mixtures, and better energy efficiency [ 30 ]. The microwave-assisted pyrolysis (MAP) process can recycle fiber from fiber-reinforced polymer (FRP) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%